Delayed Lead Perforation: Can We Ever Let the Guard Down? - Alla, Venkata M. (SAGE-Hindawi Access to Research, 2010)
Lead perforation is a major complication of cardiac rhythm management devices (CRMD), occurring in about 1%. While most lead perforations occur early, numerous instances of delayed lead perforation (occurring >30 days after implantation) have been reported in the last few years. Only about 40 such cases have been published, with the majority occurring <1 year after implantation. Herein, we describe the case of an 84-year-old female who presented with recurrent syncope and was diagnosed to have delayed pacemaker lead perforation 4.8 years after implantation. Through this report, we intend to highlight the increasing use of CRMD in elderly patients, and the lifelong risk of complications with these devices. Presentation can be atypical and a high index of suspicion is necessary for diagnosis.